Taphonomy of surface archaeological bone assemblages in coastal Patagonia: a case study - Muñoz, Sebastián (2017)
Fil: Muñoz, Sebastián. Universidad Nacional de Córdoba. Facultad de Filosofía y Humanidades. Departamento de Antropología; Argentina.